Cherax woworae, a new freshwater crayfish (Decapoda: Parastacidae) from Southwest Papua Province, Indonesia - Patoka, Jiří; Akmal, Surya Gentha; Bláha, Martin; Kouba, Antonín (Zootaxa, 2023)
Cherax woworae n. sp. is a moderately-sized burrowing freshwater crayfish endemic to the Teminabuan District, South Sorong Regency, Southwest Papua Province, Indonesia. This species is one of many freshwater crayfish species from the region that are popular ornamental animals. In the pet trade, it is commonly known as the “Blue Moon Crayfish” or “Blue Kong Crayfish”. Cherax woworae is genetically and morphologically similar to Cherax gherardii Patoka, Bláha & Kouba, 2015, but both species may be easily distinguished morphologically and by their substantial genetic divergence.